Laparoscopic vaginal vault closure with conventional straight instruments in single-port access total laparoscopic hysterectomy - Park, Daehyun; Kim, Juyoung; Jun, Hye Sun; Jeong, Hyangjin; Park, Youngse (Obstetrics & gynecology science, 2013)
Laparoscopic vaginal vault closure with conventional straight instruments is the final barrier to single-port access total laparoscopic hysterectomy (SPA-TLH). The aim of this study is to find out the safer, easier, simpler, faster, and even cheaper way to overcome it. Vaginal vault suturing techniques of 152 consecutive single-port access total laparoscopic hysterectomy cases performed by the author in Gangnam CHA Hospital, CHA University from October 1, 2003 to June 30, 2012, were retrospectively analysed with medical records and DVDs. Of 152 patients who were attempted SPA-TLH, 119 patients (78%) were finished their operations without conversion to multi-port laparoscopy or laparotomy. Of women with successful SPA-TLH, 8 cases (7%) were closed their vaginal vaults vaginally (median, 20 minutes; range, 15-44 minutes), and 111 cases (93%) laparoscopically (median, 44 minutes; range, 13-56 minutes). Laparoscopic vault closure techniques were continuous suture (4 cases, 3%; median, 36 minutes; range, 30-45 minutes), interrupted sutures using knot-pusher (7 cases, 6%; median, 52 minutes; range, 48-56 minutes) Endo Stitch suture (2 cases, 2%; median, 32 minutes; range, 13-50 minutes), continuous vault closure using percutaneous sling sutures (PCSS) (92 cases, 77%; median, 40 minutes; range, 19-56 minutes), and continuous vault closure without PCSS (6 cases, 5%; median, 23 minutes; range, 16-31 minutes). Laparoscopic vault closure using PCSS in SPA-TLH only with conventional straight instruments is the best way to overcome the barrier and the short-cut to shorten the learning curve to date.